Stories That Make History : Mexico through Elena Poniatowska's Crónicas - Stephen, Lynn (Book collections on Project MUSE., 2021)
"Lynn Stephen examines the writing of Elena Poniatowska, showing how it shaped Mexican political discourse and provides a unique way of understanding contemporary Mexican history, politics, and culture."--